6 - Anglo-Saxonism and Gallicism in Nation Building in Africa: The Case of Bilingual Cameroon and the Senegambia Confederation in Historical and Contemporary Perspective - Nicodemus Fru Awasom (Afrika Zamani, 2022)
This article is a comparative study of the impact of the colonial presence in nation building in Africa. The author argues that the colonial presence created identity markers and mindsets which sometimes facilitated but most of the time complicated the nation-building endeavours of African statesmen. The inherited Anglo-Saxon values and Gallic legacies in bilingual Cameroon on the one hand, and Senegal and The Gambia, which is located inside its belly, on the other hand, pose problems in different ways. In the case of Cameroon, the Anglo- French partition of the territory, which was originally a German protectorate, was transcended by the political elite of the two territories to achieve a reunified sovereign state in 1961 owing to a common German colonial past that generated a historical memory of one Cameroon. But Anglophone-Francophone differences in postcolonial Cameroon pose nation-building problems. In the case of Senegal and The Gambia, the British recommended close union between the two states for purposes of economic viability. But the colonially inherited values of the two states supplanted their common African ethnic bonds and militated against political integration. Thus, in both Cameroon and the Sene-Gambia, English and French colonial values constitute identity markers that pose a great challenge to nation building.